Construction and Application of a New Type of Foam Separation Equipment with the Hollow Octagonal Prismoid with Sieve Tray Inner Component - Jingli XUE; Sihan FANG; Cailiang ZHANG; Juan HAN; Jiacong WU; Lei WANG; Yun WANG (Shipin gongye ke-ji)
Objective: In this study, a novel type of the hollow octagonal prismoid with sieve tray inner component was designed to enhance liquid drainage from foam and improve the efficiency of foam separation. Methods: The model used in this work was a fermentation broth containing recombinant β-glucosidase (Glu-linker-ELP50-GB, GLEGB). The effects of structural parameters of the internal component (number, spacing, and pore diameter) and operational parameters of the foam separation experiment (temperature, initial protein concentration, gas flow rate, and liquid loading volume) on the enrichment ratio and recovery rate of GLEGB were investigated. In addition, based on the temperature sensitivity of elastin-like polypeptides (ELPs), the recombinant β-glucosidase foam solution was further purified. The structure of purified GLEGB was analyzed by circular dichroism spectrometer (CD), ultraviolet-visible spectrophotometry (UV-vis) and Fourier-transform infrared spectroscopy (FT-IR). Results: Under the optimal conditions of 5 internal components, 78 mm spacing, 2 mm pore diameter, 0.3 mg/mL initial protein concentration, 45 ℃ temperature, 200 mL/min gas flow rate and 100 mL liquid loading volume, the protein enrichment ratio of GLEGB was 2.46±0.10, 1.33 times that of the control column. After further purification of recombinant β-glucosidase foam solution, the purification ratio of GLEGB was 37.25±0.60. In addition, the results showed that the purification process did not affect the structure of GLEGB. Conclusion: The hollow octagonal prismoid with sieve tray inner component can effectively improve the enrichment ratio of GLEGB separation from fermentation liquid, which provides a new research idea for the design, research and process optimization of foam separation equipment.